Contribution analysis: An approach to exploring cause and effect - Mayne, J. (2008)
Questions of cause and effect are critical to assessing the performance of programmes and projects. When it is not practical to design an experiment to assess performance, contribution analysis can provide credible assessments of cause and effect. Verifying the theory of change that the programme is based on, and paying attention to other factors that may influence the outcomes, provides reasonable evidence about the contribution being made by the programme.